Self-rated health of university students in Germany–The importance of material, psychosocial, and behavioral factors and the parental socio-economic status - Deindl, Christian; Diehl, Katharina; Spallek, Jacob; Richter, Matthias; Schüttig, Wiebke; Rattay, Petra; Dragano, Nico; Pischke, Claudia R. (Frontiers in Public Health, 2023)
Health inequalities start early in life. The time of young adulthood, between late teens and early twenties, is especially interesting in this regard. This time of emerging adulthood, the transition from being a child to becoming an adult, is characterised by the detachment from parents and establishing of an own independent life. From a health inequality perspective, the question about the importance of the socio-economic background of parents is important. University students are an especially interesting group. Many students come from a privileged background and the question of health inequality among university students has not yet been properly studied. Based on the National Educational Panel Study (NEPS), we analysed health inequalities among 9,000 students in Germany (Ø 20 years in the first year of their studies) over a period of eight years. We found that university students in Germany report a good and very good health. Yet, we still found substantial health inequalities. Students whose parents had a higher occupational status also reported less health problems. We were also able to tie health inequality on health behaviour, psychosocial resources, and material conditions.